The collection of the Museu Casa de Rui Barbosa as a primary source for the construction of the trajectory of Maria Augusta Rui Barbosa - Lúcio de Sousa, Gabriela (2025)
This paper deals with the use of the Museu Casa de Rui Barbosa collection as a source of knowledge production about the trajectory of Maria Augusta Rui Barbosa, patron of the institution. Ten objects were highlighted and studied with the aim of tracing their life paths. Through the investigation that will be explained, the social issue of mourning and the political, historical and social insertion of the studied character were verified, according to the relationship of memory and forgetfulness that the research highlighted, in the light of the mobilized gender perspective.